From social engineering to neoliberal governance, and then what? Mapping a sustainability shift in urban planning in a medium-sized Swedish city - Sjöberg, Ida (Frontiers in Sustainable Cities, 2023)
This paper focuses on how a (assumed) entrepreneurial shift in urban planning and development has been implemented in a medium-sized city in northern Sweden, and how sustainability-as in sustainable urban development-can be argued to be a second shift in urban planning and development or represents an alternative form of neoliberal governance. To explore how and when urban entrepreneurialism and sustainability are interlinked, as well as when they are not, urban policy documents from 1988, 2007 and 2016 focusing on the development of Sundsvall city centre has been examined using thematic content analysis. The result shows that the 1988 document is significantly influenced by social democratic welfare politics, with prioritising social bonds and the Sundsvall resident being the focus, while the newer documents emphasise visitors, potential residents and architectural design to promote the flow of people, money and goods. In this sustainability is put forward as a mobilising metaphor, and serves to conceal the potential paradoxes of the priorities of the strategy, which involve the contradictions between economic, environmental and social values. Consequently, it is possible to claim that sustainability, as a concept, has acquired a new function: to disguise the less palatable consequences of growth by evoking sustainability as a guarantee of the strategy's quality, and thereby, sustainability is put to work as what I call 'entrepreneurial sustainability'.